Kolerasi Pengetahuan Budaya Lokal Suku Melayu Kotawaringin Barat Terhadap Pemahaman Pendidikan Agama Islam Peserta Didik - fathi El madani, muhammad (Mu'allim, 2024)
Local culture is positive human behavior that is directly related to nature and the environment which originates from religion, customs, ancestral advice or local culture that is developed naturally. Indonesia is a country consisting of various ethnic groups and different cultures. Indonesia is a country with a Muslim population, so local culture and religion are two inseparable things. This research aims to determine the correlation between local culture and students' understanding of Islamic religious education. The method used in this research is quantitative, the data uses simple regression data analysis techniques using SPSS (Statistical Package for the Social Sciences) software. The results of this research show that knowledge of local culture has a correlation with students' understanding of Islamic Religious Education.